2020
DOI: 10.2147/ijn.s251524
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effects Study of Isoniazid Conjugated Multi-Wall Carbon Nanotubes Nanofluid on <em>Mycobacterium tuberculosis</em></p>

Abstract: Background: Tuberculosis (TB) has always been recognized as one of the fatal infectious diseases, which is caused by Mycobacterium tuberculosis (M.tb). Isonicotinic acid hydrazide or isoniazid (INH) is one of the most commonly utilized drugs in the treatment of TB. Patients need to take 300 mg daily of INH for 6 months in combination with another anti-TB drug and tolerate several side effects of INH. On the other hand, the emergence of resistant strains of anti-TB antibiotics is one of the major problems in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“… 64 Future investigations of nanotechnology-based CS formulations in our experimental systems of macrophage polarization and LM biosynthesis might reveal if cytotoxicity and SPM-impairing effects may be circumvented. Indeed, drug delivery by nanofluids improved the efficacy of isoniazid 65 or of bromocriptine, 66 and encapsulation of a cytotoxic indirubin derivative into polymer-based nanoparticles reduced its detrimental impact on monocyte viability. 67 …”
Section: Discussionmentioning
confidence: 99%
“… 64 Future investigations of nanotechnology-based CS formulations in our experimental systems of macrophage polarization and LM biosynthesis might reveal if cytotoxicity and SPM-impairing effects may be circumvented. Indeed, drug delivery by nanofluids improved the efficacy of isoniazid 65 or of bromocriptine, 66 and encapsulation of a cytotoxic indirubin derivative into polymer-based nanoparticles reduced its detrimental impact on monocyte viability. 67 …”
Section: Discussionmentioning
confidence: 99%
“…For nanofluid preparation, 0.2 g of nano-drug powder, 6 ml of 96% ethanol, and 0.06 g of Arabic gum were added to 100 ml of deionized water. The mixture was stirred for 20 min and was placed in an ice container, and then, sonication was carried out for 20 min at 200 W 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Another study in 2020 evaluated the effects of isoniazid-functionalized MWCNTs on M. tuberculosis . Their results showed that isoniazid-functionalized MWCNTs exerted antimicrobial effects at lower concentrations compared to the usual doses of antibiotics [ 32 ]. In a recent study.…”
Section: Conclusion and Implications For Future Researchmentioning
confidence: 99%